The Phenomenon Of Celebrity Endorsement For Samsung's Brand Image And Consumer Trust - Mifthakhul Fauzi Minarso ,; Intan Natalia,; Mohamad Zein Saleh , (WANARGI : Jurnal Manajemen Dan Akuntansi, 2023)
This research discusses the influence of celebrity endorsements in marketing the Samsung brand. Celebrity endorsements have been proven to have a significant influence in influencing consumer trust, improving brand image, and increasing Samsung brand awareness. Through celebrity endorsement, the Samsung brand can take advantage of the influence and popularity of celebrities to strengthen its brand image and influence consumer perceptions positively. However, the use of celebrity endorsements also has potential risks related to the suitability of brand values, celebrity credibility, reliance on celebrities, and costs and contracts. Therefore, the Samsung brand needs to select celebrities carefully, ensure the suitability of brand values and celebrity credibility, and maintain brand consistency in the use of celebrity endorsements. By considering these benefits and potential risks, as well as managing celebrity endorsements well, the Samsung brand can leverage the power of celebrities to build a strong brand image, increase consumer trust, and generate a positive impact in marketing their products.